Synergistic effects of cyclic AMP and nerve growth factor on neurite outgrowth and microtubule stability of PC12 cells (The Rockefeller University Press, 1985)
The outgrowth of neurites from rat PC12 cells stimulated by combined treatment of nerve growth factor (NGF) with cAMP is significantly more rapid and extensive than the outgrowth induced by either factor alone. We have compared the responses of PC12 cells under three different growth conditions, NGF alone, cAMP alone, and combined treatment, with respect to surface morphology, rapidity of neurite outgrowth, and stability of neurite microtubules, to understand the synergistic action of NGF and cAMP on PC12. Surface events at early times in these growth conditions varied, suggesting divergent pathways of action of NGF and cAMP. This suggestion is strongly supported by the finding that cells exposed to saturating levels of dibutyryl cAMP without substantial neurite outgrowth initiated neurites within 5 min of NGF. This response has been adopted as a convenient assay for NGF. Neurites that regenerated in the three growth conditions showed marked differences in stability to treatments that depolymerize microtubules. The results indicate that microtubules in cells treated with both NGF and cAMP are significantly more stable than in either growth factor alone. We suggest that a shift of the assembly equilibrium favoring tubulin assembly is a necessary prerequisite for the initiation of neurites by PC12.